Emotional Intelligence Development of Students Through Tahfidz Program At Al-Amri Islamic Boarding School Probolinggo - Afkarina, Naura; M Jadid Khadavi (International Journal of Islamic Thought and Humanities, 2025)
This study aims to explore the contribution of the Tahfidz Al-Qur'an program in fostering the emotional intelligence of students (santri) at Pondok Pesantren Kyai Sekar Al-Amri, Probolinggo Regency. In the context of contemporary Islamic education, emotional intelligence is a crucial aspect in shaping the character of youth who are spiritually resilient, emotionally stable, and adaptive to the challenges of globalization and the pressures of the digital era. Using a descriptive qualitative approach with a case study method, this research illustrates how values such as patience, discipline, sincerity, and empathy are systematically internalized through structured routines, musyrif mentorship, and daily spiritual practices. The findings indicate that tahfidz is not merely a memorization activity but serves as an integral medium of character education based on Qur'anic values, effectively enhancing emotional regulation, mental resilience, and positive habits among students. This study recommends the integration of emotional aspects into the tahfidz curriculum, along with strengthening the capacity of musyrif as spiritual and emotional role models in pesantren education.